On-call hospital pharmacy services in NHS England: service provision and documentation of medicines advice calls. Issue 1 (18th June 2015) - Cheeseman, Mark P; Rutter, Paul
Abstract : Objectives: UK hospital pharmacy services have historically been delivered during typical 'office' hours, which include the provision of medicines advice via the pharmacy's medicines information department. Outside office hours, an on-call service operates whereby pharmacists handle requests for medicine supply and advice. It is not known how this out-of-hours service operates. The aim of this study was to quantify the extent and scope of its provision across England. Methods: A piloted self-administered survey was sent to every chief pharmacist in England representing acute hospitals and mental health trusts (n=218). Key findings: Just over half (n=116/218, 53.2%) of chief pharmacists returned a completed survey. Most hospitals provided an on-call pharmacy service (87.1%, n=101/116). Nearly all on-call pharmacy services (91.1%, n=92/101) provided both supply of medication and medicines advice. Two-thirds (66.2%) of pharmacists who provided on-call services were junior. The majority of trusts (83.1%, n=74/89) receive <20 calls for medicines advice per week. Hospital nurses/midwives were seen as the most common users of the on-call pharmacy service. Medicines advice was documented by on-call pharmacists all (49.5%, n=47/95) or some of the time (49.5%, n=47/95). Just under half of trusts (41.1%, n=39/95) had a standard policy for the documentation of medicines advice. Two-thirds (66.7%, n=62/93) of respondents stated that advice was documented using paper-based forms. Most trusts (81.1%, n=77/95) provided training prior to pharmacists being on-call, with medicines information pharmacists involved in nearly 80% of cases (n=61/77) (respondents could select more than one option). Conclusions: Medicines advice is an integral part of the pharmacy on-call service, which was provided by junior staff. Variability existed in resourcing the service across trusts. In addition to existing standards for documentation of medicines advice, professional standards should be developed for on-call hospital pharmacy service provision and training.